2012
DOI: 10.1038/nchem.1454
|View full text |Cite|
|
Sign up to set email alerts
|

Alteration of the oxygen-dependent reactivity of de novo Due Ferri proteins

Abstract: De novo proteins provide a unique opportunity for investigating the structure-function relationships of metalloproteins in a minimal, well-defined, and controlled scaffold. Herein, we describe the rational programming of function in a de novo designed di-iron carboxylate protein from the due ferri family. Originally created to catalyze O2-dependent, two-electron oxidation of hydroquinones, the protein was reprogrammed to catalyze the selective N-hydroxylation of arylamines by remodeling the substrate access ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
156
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(161 citation statements)
references
References 44 publications
5
156
0
Order By: Relevance
“…55,56 In each case, the crystallographic and NMR studies showed the proteins folded into their designed conformations, which recapitulated the main structural features of much larger and more complex diiron proteins. 810,57 A highly symmetrical starting protein was used in the initial design, but this symmetry was eliminated in subsequent functional studies in which the coordination environment of each metal ion was systematically varied. 1012,5759 The DF scaffold was ultimately exploited to examine the structural requirements for two-electron and four-electron reduction of dioxygen with concomitant substrate oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…55,56 In each case, the crystallographic and NMR studies showed the proteins folded into their designed conformations, which recapitulated the main structural features of much larger and more complex diiron proteins. 810,57 A highly symmetrical starting protein was used in the initial design, but this symmetry was eliminated in subsequent functional studies in which the coordination environment of each metal ion was systematically varied. 1012,5759 The DF scaffold was ultimately exploited to examine the structural requirements for two-electron and four-electron reduction of dioxygen with concomitant substrate oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…26 The addition of an extra metal-binding residue and adjusting the substrate cavity switch a due ferri protein originally intended to oxidize hydroquinones to catalyze the selective N-hydroxylation of arylamines. 27 While design efforts focused on metal-free enzymes have yielded many useful in silico tools, these tools are insufficient for metal-containing enzymes. [28][29][30] When designing metalloenzymes, it is critical to properly treat the electronic structure of the metal.…”
Section: Introductionmentioning
confidence: 99%
“…These progresses have been driven by underlying computational or rule-based design methods, which can be stringently calibrated through the de novo design of amino acid sequences that fold into desired three-dimensional structures 4,[8][9][10] . In this regard, rule-based designs have attained some remarkable successes 7,11,12 , albeit limited to particular types of target structures or structure motifs. More general methods such as RosettaDesign 13 are based on minimizing an effective energy function, which has been, for large parts, derived from molecular mechanics force fields 4 .…”
mentioning
confidence: 99%
“…I n recent years, protein design has achieved some milestone successes with profound implications in biosciences and biotechnology [1][2][3] , including the designs of a novel protein fold 4 , new biomolecular interactions and regulations 5 , as well as new biocatalysts 6,7 . These progresses have been driven by underlying computational or rule-based design methods, which can be stringently calibrated through the de novo design of amino acid sequences that fold into desired three-dimensional structures 4,[8][9][10] .…”
mentioning
confidence: 99%